Prepubertal acne: A retrospective study - Cécile Frénard, MD; Siham Mansouri, MD; Stéphane Corvec, MD-PhD; Aurélie Boisrobert; Amir Khammari, PhD; Brigitte Dréno, MD-PhD (Wolters Kluwer, 2021)
Background: Acne vulgaris is a common skin disorder, but studies on the epidemiologic features of prepubertal acne are limited. Objectives: The aim of this study was to determine the prevalence and severity of prepubertal acne and to identify factors influencing acne severity and poor response to treatment. Methods: A retrospective study was conducted on 683 patients with acne from our database who visited the dermatology department of Nantes University hospital between October 2014 and May 2018. Patients of prepubertal acne (7-12 years) were included in this study. Results: Of the 683 patients with acne, 24 (3.5%) had prepubertal acne. Prepubertal acne was more common in female patients (75%). Acne severity assessment showed that severe acne (Groupe Expert Acné global acne severity scale 4) was the most common form (33%), and mild and moderate forms (Global Evaluation Acne Group, global acne severity scales 2 and 3) accounted for 25% each. There was a high predominance of phylotype IA1 of Cutibacterium acnes (belonging to CC18 subgroup). The analysis of patients' lifestyle and acne features identified three factors associated with an increased risk of poor response or resistance to acne treatment. Initially severe acne grading (grade 4) was the most strongly associated parameter (p < .028), followed by regular milk consumption and taking other medications in addition to acne treatment (p < .049 for each). Conclusion: This study reported on prepubertal acne features and identified three factors associated with a high risk of treatment failure or relapse. Adequate and prompt treatment is needed in this subgroup of patients to minimize disease burden and prevent subsequent disease worsening.